If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-11=79
We move all terms to the left:
6x-11-(79)=0
We add all the numbers together, and all the variables
6x-90=0
We move all terms containing x to the left, all other terms to the right
6x=90
x=90/6
x=15
| 36=-3(1-x)+4(x+1) | | 18x+x=5 | | 2x+2=5x–19 | | y/4+3.3=3.1 | | 3x-5(x-5)=-9+3x+24 | | 92=7x- | | 11+7x=32 | | -15.7=c/5-3.2 | | -13=2v-7 | | 15p-14p=8 | | 7/8x+3=17 | | 286=22-v | | -0,4(х-2)+2,2=0,5(3x+2) | | 17b-14b=6 | | -0.4(х-2)+2.2=0.5(3x+2) | | 9x-(6x-14)=38 | | 6p=270 | | w/15=27 | | 25z=850 | | 2w=384 | | p/25=18 | | 11s=946 | | g/21=16 | | 1/6x+1/8x+5+1/12x+6=1/2x | | -6.1=11.4+v/7 | | p/23=22 | | -3(2x-4)-6=-(5x+4) | | u24=22 | | 3v=366 | | 214=2g | | 648=8r | | 8h=824 |